Prevalence of blaOXA genes in carbapenem-resistant Acinetobacter baumannii isolates from clinical specimens from Nopparatrajathanee Hospital - Sawanya Pongparit; Adun Bunchaleamchai; Naiyana Watthanakul; Nonthawat Boonma; Kothchakron Massarotti; Supreeya Khamuan; Nutchodchapan Ingkasamphan; Kansini Wannasin (Journal of Current Science and Technology, 2021)
This study aimed to investigate the prevalence of blaOXA genes in carbapenem-resistant Acinetobacter baumannii (CRAB) isolates from Nopparatrajathanee Hospital and the resistance rate against antimicrobial agents used for A. baumannii treatment. The susceptibility of 170 CRAB isolates, obtained from July to October 2018 at Nopparatrajathanee Hospital, was tested against seven antimicrobial agents by the disk diffusion method. While the susceptibility to colistin was determined by the broth microdilution method. The distribution of carbapenem-resistant genes of blaOXA-51-like, blaOXA-23-like, blaOXA-58-like, and blaOXA-24-like in the CRAB isolates was determined using a multiplex polymerase chain reaction. The MBL-type carbapenemase genes and ISAba1-blaOXA-51-like gene in the CRAB isolates were also detected using conventional PCR. The majority of CRABs (99.42%) were non-susceptible to more than three antimicrobials categories, and 31.18% of CRABs were extensively drug-resistant. Most CRAB isolates (99.42%) were non-susceptible to more than three categories of antimicrobial agents, and 31.18% of CRAB were extensively drug-resistant. Although colistin and tigecycline were the two most effective antimicrobial agents, the resistance rates were 7.06% and 4.12%, respectively. All isolates had the intrinsic resistance gene of A. baumannii, the blaOXA-51-like gene. The frequencies of blaOXA-51-like with blaOXA-23-like; blaOXA-51-like with blaOXA-24-like; blaOXA-51-like with blaOXA-23-like and blaOXA-58-like; and ISAba1-blaOXA-51-like were 77.06%, 4.71%, 3.53%, and 14.12%, respectively. None of the isolates were positive for MBL-type carbapenemase genes. This research showed that the dominant carbapenems resistance gene among the CRAB in this hospital was blaOXA-23-like. It also confirmed the horror of drug resistance problems for A. baumannii with limited treatment options, which should raise everyone's awareness.